2022
DOI: 10.1001/jamanetworkopen.2022.25424
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rates of Brain Metastases and Association With Breast Cancer Subtypes in Ontario, Canada

Abstract: This cohort study describes clinical cumulative incidence of brain metastases among patients with de novo metastatic breast cancer using population health administrative databases in Ontario, Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, almost half (49.4%) had an unknown molecular subtype. 4 In comparison, in our study, 31.1% of patients had an unknown molecular subtype, including 21.1% of the BrM cohort. A metanalysis from Kuksis et al reported that the pooled CI of BrM in metastatic BC patients was approximately 31% in ERBB2+, 32% in HR-negative/ERBB2-, and 15% in the HR+/ERBB2-cohorts.…”
Section: Discussionmentioning
confidence: 45%
“…However, almost half (49.4%) had an unknown molecular subtype. 4 In comparison, in our study, 31.1% of patients had an unknown molecular subtype, including 21.1% of the BrM cohort. A metanalysis from Kuksis et al reported that the pooled CI of BrM in metastatic BC patients was approximately 31% in ERBB2+, 32% in HR-negative/ERBB2-, and 15% in the HR+/ERBB2-cohorts.…”
Section: Discussionmentioning
confidence: 45%
“…Although there was no difference in the overall number of systems with metastasis, the reticuloendothelial and digestive systems were significantly more frequently involved in the BRCA2 carriers compared with non‐carriers with prostate cancer. This observation of a predilection for certain organ systems in carriers with specific tumour subtypes, in addition to the hypothesis of the microenvironment supporting a shorter time for metastatic tumour growth in some organs, as described in brain metastases, 29,30 highlights the opportunity to define these underlying mechanisms. Further interrogation of the autopsy samples together with the differences in the ‘soil’ of the sites will help to identify the key processes that drive the observed differential tumour metastases and help in the recognition of potential new pathways for treatments.…”
Section: Discussionmentioning
confidence: 89%
“…Approximately 45% of patients diagnosed with advanced TNBC develop distant metastasis to CNS and/or visceral organs, with a median OS of 13.3 months [ 23 ]. Another study indicated that the TNBC subtype is significantly correlated with a shorter time between the diagnosis of metastasis and treatment for brain metastasis with radiotherapy, with a median time of 7.5 months [ 24 ]. Consistently, our TNBC cohort had a higher proportion of patients with metastases than the non-TNBC group, with more metastatic sites and brain metastases, demonstrating the metastatic ability of TNBC.…”
Section: Discussionmentioning
confidence: 99%